Acute cerebellar ataxia associated with enteric fever in a child: a case report - İncecik, Faruk; Hergüner, M, Özlem; Mert, Gülen; Alabaz, Derya; Altunbaşak, Şakir (The Turkish Journal of Pediatrics, 2013)
Enteric fever is a common infectious disease of the tropical world. Characteristic presenting features include fever, relative bradycardia, diarrhea or constipation, and abdominal pain. Central nervous system involvement is not rare and has a wide spectrum of presentation in enteric fever. Complications such as meningism, delirium, coma, and convulsions have been reported often. However, isolated acute cerebellar ataxia associated with enteric fever is rare. Here, we report a seven-year-old boy with enteric fever who presented with acute cerebellar ataxia. Following treatment with appropriate antibiotics, the patient showed complete recovery over the next four weeks.